COVID-19 Impact on Students in Physical Therapist and Physical Therapist Assistant Education Programs in New York and New Jersey: Key Issues and Recommended Responses. Issue 4 (8th December 2021) - Hyland, Nannette; Vore, Mary Ellen; Chan, Clarence; Katz, Joanne; Rivers, Lynn; Hewson, Kyle
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: In March 2020, after the COVID-19 pandemic surged in New York City, higher education had to either halt or immediately convert to fully online education. Physical therapy program directors in New York (NY) State and New Jersey (NJ) immediately recognized a need to understand the new challenges facing students. Purpose: The purpose of this paper was to identify the challenges that students in physical therapist (PT)/physical therapist assistant (PTA) programs in NY and NJ were experiencing and how institutions could respond to those challenges. Subjects: Students enrolled in a PT or PTA program in NY or NJ; N = 934 (861 PT and 73 PTA). Methods: An online survey was distributed to PT/PTA programs in NY/NJ. The survey consisted of open-ended and closed-ended questions related to academic, financial, and nonacademic issues, transition to online learning, and how institutions could respond to student challenges. Descriptive statistics and thematic analysis were used. Results: The most important challenges that students identified were quality/quantity of hands-on experiences, lack of contact with classmates, personal physical and mental health/wellness, and affording tuition and fees. Some differences were found across geographical regions and graduating cohorts. Physical therapist and PTA student cohorts had the same top concerns. Five major themes emerged from open-ended questions: communication; safe return to campus for psychomotor skills; additional academic resources; recognition of students' financial, mental, and physical health concerns; and, financial support. Discussion and Conclusion: Students in physical therapy education in NY and NJ faced similar challenges because of COVID-19 as observed by other universities worldwide. Physical therapy education can be stressful, and these additional challenges made this time extremely difficult. The findings of this survey can be used to develop a crisis management plan for university emergencies that require program modifications.